Studies on the mycoflora associated with the leaves of some plants - D. A.*, Dhale (Current Botany, 2011)
About twenty four diseased plants were collected from around Aurangabad city of Maharashtra State. The mycoflora on the leaf surfaces was observed by various methods such as direct observation on stained leaf, leaf wash method, spore fall method, leaf print method. About fifteen genera of different pathogenic fungi have been recorded. Potato dextrose agar media was used for growing the fungi. The some fungi which recorded are Alternaria spp., Aspergillus niger, Aspergillus flavus, Cladosporium spp., Fusarium spp., Helminthosporium spp., Phytopthora spp., Pythium spp., Phyllactinia spp, Uncinulla spp., Urosystis spp., Uromyces spp., etc. The maximum infection is by Fussarium spp. and Alternaria spp. to 13 plant species. The pathogen Fussarium spp. and Alternaria spp. are found causing disease both on same host on up to 9 different plant species.